Metagenomic analysis of gut microbiota composition and function in wild mice (Rattus flavipectus) infected with Enterocytozoon bieneusi - Yu, Hai-Long; Liu, Rui; Wang, Hai-Tao; Hou, Qing-Yu; Qin, Ya; Yang, Xing; Gao, Zhen-Qiu; Yang, Li-Hua; Zhao, Quan; Ma, He (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundEnterocytozoon bieneusi (E. bieneusi) is a pathogenic microsporidian that infects a variety of hosts, including wild mice, potentially influencing their gut microbiota. This study aims to explore how E. bieneusi infection influences the gut microbiota composition and function in wild mice.MethodsFecal samples were collected from 20 wild mice (Rattus flavipectus) in September 2023 in Yunnan Province, China. The PCR results showed that 10 were infected with E. bieneusi and 10 were uninfected, with no samples testing positive for Cryptosporidium spp., Blastocystis, Giardia, Cyclospora or Balantioides coli. DNA was extracted and subjected to metagenomic sequencing using Illumina HiSeq. Gut microbiota composition was assessed using MetaPhlAn4 for species-level annotation. The contigs were used to construct a gene catalog and perform functional annotation. Additionally, viral sequences were identified by analyzing the contigs with software, such as CheckV and Vibrant.ResultsThe gut microbiota diversity showed no significant difference between mice infected with E. bieneusi and the control group, with the dominant phyla being Firmicutes and Bacteroidetes. Virome analysis identified 18,192 high-quality viral sequences, with the E. bieneusi group exhibiting higher viral species diversity. Furthermore, significant differences were observed in 178 viral operational taxonomic units (vOTUs) between the two groups, with 161 vOTUs enriched in the E. bieneusi group. Functional analysis demonstrated significant enrichment of several metabolic pathways in the gut microbiota of wild mice infected with E. bieneusi, particularly in the metabolism of terpenoids and polyketides, digestive system, biosynthesis of other secondary metabolites and metabolism of cofactors and vitamins. Notably, unique virus-bacteria correlations were observed in the E. bieneusi group.ConclusionsE. bieneusi infection significantly alters the gut virome in wild mice, affecting microbial composition and interactions. The infection appears to drive adaptive changes in microbial functions, especially in metabolic processes, suggesting a host response to infection-related stress.